Health-promoting skills for children: Evaluating the influence of a media literacy and food marketing intervention. (June 2020) - Truman, Emily; Elliott, Charlene
Background: Media literacy skills are needed to navigate high levels of food marketing promoting the consumption of unhealthy foods. Health-promoting media literacy education encourages children to use analytical skills to critically examine media messages in order to make informed health choices. Objective: To evaluate the influence of media literacy lesson plans for children focusing on critical knowledge around food marketing. Design: Evidence-based Media Literacy & Food Marketing lesson plans, designed for grades 3 to 6 (ages 8–11) and 6 to 9 (ages 11–14), were developed to fill the knowledge gaps children demonstrated with respect to assessing of the healthfulness of packaged foods. Setting: Two public schools in Calgary, Alberta, Canada. Methods: An educational intervention with pre-test/post-test design. The lesson plans were used by teachers in the classroom, and a questionnaire was created to assess children's pre- and post-lesson levels of critical knowledge about food marketing. Results: In total, 71 students from grades 5, 7, 8 and 9 participated. Qualitative analysis of responses showed increased analysis and evaluation skills when it came to understanding of food marketing appeals, and increased ability to assess the nutritional content of packaged foods. Conclusion: This study is novel in its use of media literacy as a framework for understanding food packaging appeals. It highlights the importance of examining procedural and interpretive knowledge in the evaluation of critical media literacy skills around food. This allows researchers, educators and health practitioners to better gauge how children are able to apply nutrition information in different contexts to make informed food choices.